Criação de zonas de alta permeabilidade em fraturas: modelagem numérica do Lajedo de Soledade, Formação Jandaíra, Bacia Potiguar - Rabelo, Juliana Gomes (2014)
The fracturing in carbonate rocks has been attracting increasingly attention due to new oil discoveries in carbonate reservoirs. This study investigates how the fractures (faults and joints) behave when subjected to different stress fields and how their behavior may be associated with the generation of karst and consequently to increased secondary porosity in these rocks. In this study I used satellite imagery and unmanned aerial vehicle UAV images and field data to identify and map faults and joints in a carbonate outcrop, which I consider a good analogue of carbonate reservoir. The outcrop comprises rocks of the Jandaíra Formation, Potiguar Basin. Field data were modeled using the TECTOS software, which uses finite element analysis for 2D fracture modeling. I identified three sets of fractures were identified: NS, EW and NW-SE. They correspond to faults that reactivate joint sets. The Ratio of Failure by Stress (RFS) represents stress concentration and how close the rock is to failure and reach the Mohr-Coulomb envelopment. The results indicate that the tectonic stresses are concentrated in preferred structural zones, which are ideal places for carbonate dissolution. Dissolution was observed along sedimentary bedding and fractures throughout the outcrop. However, I observed that the highest values of RFS occur in fracture intersections and terminations. These are site of karst concentration. I finally suggest that there is a relationship between stress concentration and location of karst dissolution in carbonate rocks.